Peyzazh Shemetovo - Makovsky, Vladimir Yegorovich (Pravda, 1956)
Artwork; landscape painting of Shemetovo village 1956 reproduction of painting 'Shemetovo landscape' by V. Makovsky. Original title: Пейзаж Шеметово PO-0418